Leaf area of whole and damaged coffee leaves (Coffea arabica L.) determined by leaf dimensions and digital imaging - Flumignan, Danilton Luiz; Adami, Marcos; Faria, Rogério Teixeira de (Coffee Science - ISSN 1984-3909)
Leaf area (LA) is an indicative of crop yield and is required in most agronomic and physiological studies. In this work, two methods to measure coffee leaf area, one based on leaf dimensions and the other on digital imaging, were compared to the standard LI-COR method, using whole and damaged leaves. The digital image measurements, taken in the lab (destructive sample) and in the field (non-destructive sample), were also compared. It was concluded that the leaf dimensions based method estimated adequately the LA of whole leaves, but was not suitable for damaged leaves. The digital imaging method measured, with great precision, the LA of both, whole and damaged leaves. Therefore, this method can substitute the LI-COR method, with the advantage of being non-destructive, low cost and portable.